ANALISIS YURIDIS PERTANGGUNGJAWABAN PIDANA PEMBUAT STEMPEL YANG DIPERGUNAKAN KONSUMEN UNTUK TINDAK PIDANA DIKAITKAN DENGAN AJARAN KAUSALITAS - Fauziah, Putri; Effendi, Erdianto; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In the Penal Code (Penal Code) article 263 governs the crime of mail forgery. There are several actions that belong to the type of mail forgery, one of which is the creation of stamps that can cause the stamp maker to also be held accountable. But in reality, the stamp was only used as a means of evidence in the trial. This is known from the example of the Case Verdict Number: 1293/Pid.B/2018/PN. Pekanbaru with defendant Agus Salim Ahim, Number:325/Pid.B/2013/PN. Pekanbaru with defendant Masrizal, and Number: 423/Pid.B/2017/PN. Pekanbaru with defendant Madi Permana Sesa states that the stamp is only used as a tool of evidence seized for destruction. Criminal liability is often also associated with the doctrine of causality. Causality is used as a "filter" in establishing a person's criminal accountability. As a filter, causality will filter out any factual actions committed by the perpetrator, after the factual action is netted the next will be sought legal action. By finding his legal action, a person will be held accountable.The crime of stamp forgery is already very detrimental to society. Many stamps from various government agencies are often forged by the public and even State officials. Not all actions proven by the elements can lead to the perpetrator being punished if he or she cannot be blamed so criminal responsibility cannot be held. In practice many cases involving people in good faith are also held responsible for such crimes. One of them is a stamp maker. But as the basis of the judge's consideration in making a verdict is generally the same. The purpose of writing this thesis is; first, To know the accountability of stamp makers that consumers use for criminal acts is associated with the doctrine of causality. Secondly to know the consequences of the breadth of criminal liability is associated with the doctrine of causality. This type of research is normative research, using an analytical approach. This method of thesis writing research uses normative juridical methods.Keywords :Criminal Liability, Forgery, Stamp Maker, Doctrine Of Causality